The expectations of young people of last year of secondary school about the future: theoretical–methodological decisions about the construction of data: Decisiones teórico- metodológicas sobre la construcción de los datos y el trabajo de campo. (Itinerarios Educativos, 2024)
This work is part of a research that investigates the future expectations, the meanings about education and work of young people in the last year of secondary school in the city of Paraná, capital of the province of Entre Ríos, in the period between years 2023-2024.Its objective is to account for the theoretical-methodological decisions adopted regarding the construction of the data - the choice of a questionnaire as an instrument for obtaining information - and the procedure for the selection, structure and size of the sample. The study was carried out in 22 secondary schools – oriented and technical-vocational – of state and private management in the city of Paraná, with a total of 559 students.At a methodological level, the research contemplates a multidimensional design that, in addition to the students' opinions, analyzes educational policy and institutional strategies for preparation for graduation.
Keywords: Expectations- young people- secondary school- theoretical-methodological decisions